Contemporary business mathematics for colleges - Deitz, James E.; Southam, James L. (Cengage Learning, 2016)
"Presenting a basic, arithmetic-based approach, Contemporary business mathematics for colleges, 17E uses step-by-step development of concepts, hands-on practice exercises, and real-world application of techniques to effectively prepare students for careers in business. Practical skill-building applications are emphasized throughout as the text progresses, from the most basic to more complex business math topics. Numerous problems and examples are taken from actual businesses. Self-check features such as end-of-section Concept Checks, end-of-chapter Bottom Lines, and end-of-chapter Review Problems enable students to test their understanding before advancing to other topics or completing assignments. CengageNOW offers an online homework solution option with fully algorithmic end-of-chapter problems students can use to drill again and again to build their math confidence." -- Publisher's description